Migration, Crisis and Adjustment in an Enlarged E(M)U: The Spanish Perspective - Núria Rodríguez-Planas; Lídia Farré (Institute for the Study of Labor (IZA), 2014)
This paper investigates the labour market and welfare changes experienced by enlarged-EU migrants before and after 2007. For this purpose, we briefly review the Spanish socio-economic institutional background, as well as its migration policy towards enlarged-EU citizens. Then we discuss the importance of inflows and stocks of enlarged-EU migrants in Spain, including their socio-demographic, labour market and welfare use characteristics. We proceed to evaluate the impact of enlarged-EU migrants on the Spanish labour market and the welfare state, with particular attention paid to how the situation has changed for enlarged-EU migrants after 2007, in relation to other migrants and natives. After investigating the effects of enlarged-EU migrants on the native population, the paper concludes with a discussion on lessons learned.
Keywords: J15; J24; J61; J62; 330; immigration; EU enlargement; Great Recession